2005
DOI: 10.1016/j.ymthe.2005.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Gene Transfer to Alveolar Septa for Effective Suppression of Lung Fibrosis

Abstract: We examined therapeutic gene transfer of human hepatocyte growth factor (hHGF) to alveolar septa in mouse bleomycin-induced lung fibrosis using macroaggregated albumin-polyethylenimine complex (MAA-PEI). Intravenous administration of MAA-PEI along with 1 microg pCAG.hHGF to C57BL/6 mice increased the uptake of plasmids into alveolar capillary endothelial cells and epithelial cells, prolonged hHGF expression in the lung, and induced a level of hHGF expression equal to that seen with 10 microg of hHGF-expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
57
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 38 publications
1
57
0
Order By: Relevance
“…The role of HGF as a potent antifibrotic factor has recently been established in several animal models of pulmonary fibrosis (21)(22)(23)(24). However, the therapeutic potential of HGF in the treatment of pulmonary fibrosis in humans has yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of HGF as a potent antifibrotic factor has recently been established in several animal models of pulmonary fibrosis (21)(22)(23)(24). However, the therapeutic potential of HGF in the treatment of pulmonary fibrosis in humans has yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…In the lung, HGF acts as an important mediator of mesenchymal-epithelial interactions during development, inflammation, and repair (18,22). Recently, HGF was shown to reverse fibrogenic processes in a bleomycin-induced model of pulmonary fibrosis (21)(22)(23)(24). HGF inhibits collagen deposition and attenuates the amount of already deposited extracellular matrix proteins (21,23).…”
mentioning
confidence: 99%
“…Blocking HGF by inhibitory antibodies worsens lung fibrosis after bleomycin administration (14). Elevation of HGF levels by its exogenous delivery (22,23) or by gene transfer (24) reduces the amount of fibrosis that occurs after lung injury. This antifibrotic effect is not unique to the lung, but occurs in other organs, including liver (51), kidney (52,53), skin (54), and heart (55).…”
Section: Discussionmentioning
confidence: 99%
“…These increases are significant because inhibition of HGF activity in the lung in animal models worsens lung fibrosis (14). Conversely, interventions designed to increase HGF reduce scarring (22)(23)(24). For HGF to have its effect on target cells, it must undergo several extracellular processing events (15,16).…”
mentioning
confidence: 99%
“…Numerous studies have shown HGF to be an endogenous antifibrotic factor in the lungs, ameliorating fibrotic lesions and preserving lung function in experimental animal models of pulmonary fibrosis (22)(23)(24)(25). HGF exerts its antifibrotic effects on pulmonary function by reducing the production of type I collagen and CTGF, and increasing the production of matrix metalloproteinase 1 in lung fibroblasts (12,26).…”
Section: Discussionmentioning
confidence: 99%